PROBLEM-BASED LEARNING IN CHEMISTRY EDUCATION: ITS IMPACT ON UNIVERSITY STUDENTS’ CRITICAL THINKING SKILLS IN INDONESIA - Mukni'ah (Indonesian Journal of Education (INJOE), 2026)
This study aims to analyze the application of Problem-Based Learning (PBL) in chemistry education and its impact on students' critical thinking skills in Indonesian universities. The research uses a qualitative approach with a literature study method through searching for articles on Scopus, Web of Science, ScienceDirect, ERIC, and Google Scholar published in the period 2021–2026. The literature selection process was carried out in a structured manner based on the principles of PRISMA 2020 by considering the suitability of the topic, the context of higher education, the application of PBL, and the measurement of critical thinking skills. Data were analyzed using thematic content analysis through the stages of reduction, grouping, comparison, interpretation, and synthesis. The results of the study show that PBL consistently has a positive influence on students' ability to interpret problems, analyze information, evaluate evidence, formulate inferences, provide scientific explanations, and self-regulation. The effectiveness of PBL is strongest when learning uses authentic problems, investigative activities, collaborative discussions, solution presentations, metacognitive reflection, and technology support. However, the impact of PBL is not uniform because it is influenced by initial knowledge, student motivation, group dynamics, problem quality, lecturer facilitation ability, duration of intervention, and assessment instruments used. This study concludes that PBL is a relevant approach to strengthen critical thinking skills in chemistry learning, but its implementation requires systematic planning, scaffolding, and evaluation. Further research is recommended to use more robust experimental designs, cross-university samples, longer durations, and standardized critical thinking instruments so that the findings have better validity and generalization. These findings provide a conceptual basis for lecturers and study program managers to design chemistry learning that is contextual, participatory, evidence-based, inclusive, sustainable, and oriented towards complex real-world problem-solving.